Sodium dirubidium citrate, NaRb(2)C(6)H(5)O(7), and sodium dirubidium citrate dihydrate, NaRb(2)C(6)H(5)O(7)(H(2)O)(2) - Cigler, Andrew J. (International Union of Crystallography, 2019)

(untitled) (Acta Crystallogr E Crystallogr Commun)
The crystal structures of sodium dirubidium citrate {poly[μ-citrato-dirubidium(I)sodium(I)], [NaRb(2)(C(6)H(5)O(7))](n)} and sodium dirubidium citrate dihydrate {poly[diaqua(μ-citrato)dirubidium(I)sodium(I)], [NaRb(2)(C(6)H(5)O(7))(H(2)O)(2)](n)} have been solved and refined using laboratory X-ray powder diffraction data, and optimized using density functional techniques. Both structures contain Na chains and Rb layers, which link to form different three-dimensional frameworks. In each structure, the citrate triply chelates to the Na(+) cation. Each citrate also chelates to Rb(+) cations. In the dihydrate structure, the water molecules are bonded to the Rb(+) cations; the Na(+) cation is coordinated only to citrate O atoms. Both structures contain an intramolecular O—H⋯O hydrogen bond between the hydroxy group and one of the terminal carboxylate groups. In the structure of the dihydrate, each hydrogen atom of the water molecules participates in a hydrogen bond to an ionized carboxylate group.